Entrepreneurial Knowledge, Social Media, and Innovation on the Success of MSMEs - Alma Karennina; Rininda, Bella Puspita; Ines Saraswati Machfiroh; Radna Nurmalina; Mufrida Zein (Jurnal Penelitian Ekonomi Dan Akuntansi, 2025)
This research aims to evaluate the impact of entrepreneurial knowledge, social media usage, and innovation on the success rate of SMEs. The method applied in this research is a quantitative approach, with primary data collected through questionnaires. The research sample consists of 84 SMEs operating in the coffee shop sector in South Kalimantan, selected using random sampling techniques with the Slovin formula to ensure representativeness. The data obtained were analysed using multiple linear regression tests to identify the relationship between independent and dependent variables. The research findings indicate that entrepreneurial knowledge does not have a significant impact on the success of SMEs. At the same time, the use of social media and innovation has been proven to significantly influence the success of SMEs.